Morphological characterization, fungicidal alternatives and biological control of Peronospora farinosa on chamomile - M. M. Mergawy; M. M. H. Hassanin; A. A. M. Ali; Heba Yousef (Egyptian Journal of Biological Pest Control, 2023)
Abstract Background Chamomile (Matricaria chamomile L.) is one of the very important medicinal plants worldwide, particularly in Egypt. The downy mildew disease is considered one of the most important diseases of chamomile. Peronospora farinose was identified as the causal pathogen of downy mildew of infected chamomile plants, collected from Fayoum Governorate, Egypt, during 2022. Results Efficiency of some fungicidal alternatives for management of downy mildew disease on chamomile leaves was evaluated in vitro studies using detached leaves technique. Each of the biocide, Bio-Cure F and Thyme oil emulsion treatments, before and after the fungal inoculation, respectively, was the best effective treatments, which reduced disease incidence to the lowest percentages. However, the treatment of Bio-Cure F before the fungal inoculation had the superiority for reducing disease severity to the lowest percentage, followed by Thyme oil emulsion, after the fungal inoculation. On the other hand, under greenhouse conditions, the best treatment reduced disease incidence and disease severity to the lowest percentages was Thyme oil emulsion, followed by Bio-Cure F, after and before the fungal inoculation, respectively. Total sugars content was obviously lower in treated chamomile plants before and after the fungal inoculation than in untreated controls. On the contrary, free phenols were obviously higher in treated chamomile plants before and after the fungal inoculation than in untreated controls. Conclusion The present study indicated the possibility of using Bio-Cure F (biocide) and Thyme essential oil emulsion as spraying treatment against P. farinosa on chamomile plants.